Karlheinz Stockhausen’s stage cycle Licht. Musical theatre of the world - Draus, Agnieszka (Interdisciplinary Studies in Musicology, 2018)
The main idea of the paper is a presentation of the stage cycle Licht, absorbing the composer for over one-third of his active creative life. The question arises as to the generic affiliation of Stockhausen’s opus magnum: close to operatic works by Luciano Berio and Mauricio Kagel or to pop productions of works by Philip Glass? Analysing the subject matter and content of Licht, as well as its message and the means of expression employed, it is difficult not to discern the unification, within a single work, of what might appear to be contrasting musical genres and kinds of theatre (mystery play, expressionist drama, happening). It is worth remembering that the composer himself does not employ any specific generic term except for Opernzyklus. He often, however, refers to the forms and genres of theatre, cultivated in many different parts of the world, which have inspired him (e.g. in Malaysia, Japan, Bali, the USA), and he admits to the evolution of his views on faith. Can the substance of Licht be reduced to a common denominator? Can the heptalogy be called ‘sacred’ theatre? Or - on the contrary - an extremely profane, ‘pagan’ avant-garde spectacle?